Small Nations and Colonial Peripheries in World War I - Barry, Gearóid; Dal Lago, Enrico; Healy, Róisín (History of Warfare, 2016)
This edited volume examines World War I comparatively in both small nations and colonial peripheries. Chapters address subject nations within Europe such as Ireland and Poland; neutral states, such as Sweden and Spain; and colonies like German East Africa.; Readership: Academics and non-academics interested in the First World War, military history, modern European history, small European states, Europe's colonial empires, transnational transfers and ethnic identity.